The impact of clopidogrel combined with aspirin or aspirin alone on prognosis and adverse events in patients undergoing coronary artery bypass grafting in the first month after surgery - Li, Haiming; Hu, Hui; Li, Jingxing; Gu, Chengxiong; Li, Bo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary artery bypass grafting (CABG) was a critical intervention for patients with obstructive coronary artery disease, yet managing thrombotic complications post-surgery remains challenging. Aspirin was the standard antiplatelet therapy following CABG; however, the potential benefits of dual antiplatelet therapy (DAPT) with clopidogrel were not well-defined in this setting. This study evaluates the impact of DAPT compared to aspirin alone on prognosis and adverse events in the first month after CABG.MethodsThis retrospective cohort study analyzed data from 281 patients undergoing CABG from August 2020 to July 2023. Using propensity score matching (PSM), these patients were separated into two groups based on their postoperative medication: the aspirin alone group (ASA, n = 117) and the dual antiplatelet therapy group (DAPT, n = 117). PSM ensured balanced baseline characteristics. Graft patency, platelet function, and postoperative adverse events were evaluated, with statistical significance set at a P-value < 0.05. Categorical variables were reported as frequencies and percentages [n (%)] and analyzed using Chi-square test. Continuous variables with a normal distribution were presented as mean ± standard deviation (SD) and analyzed using t test.ResultsDAPT resulted in significantly lower rates of saphenous vein graft occlusion compared to aspirin alone (17.09% vs. 29.06%, P = 0.030). Inhibition of platelet aggregation (IPA) was enhanced in the DAPT group (64.35% vs. 62.46%, P = 0.010), and thromboxane B2 levels were consistently lower on days 7, 14, and 30 post-surgery (P = 0.009, P = 0.005, and P = 0.002, respectively). Although adverse cardiovascular events did not significantly differ, minor bleeding, such as epistaxis, was more common in the DAPT group (6.84% vs. 0.85%, P = 0.041). Regression analysis showed DAPT reduced the odds of adverse events (OR: 0.452, 95% CI: 0.253–0.816, P = 0.008).ConclusionDAPT with clopidogrel and aspirin improves graft patency and platelet inhibition in the first month following CABG, though it was associated with increased minor bleeding events.